2015
DOI: 10.1016/j.ijrmms.2015.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of large localized damage structures forming ahead of an active mining front by using advanced acoustic emission mapping techniques

Abstract: a b s t r a c tWe applied advanced mapping techniques to 291 230 acoustic emission (AE) events as small as around M À 4 that were recorded over 50 days by an ultra-high resolution network close to the active front of a tabular mining stope being advanced northward at 1 km depth in the Cooke 4 Gold Mine in South Africa. We first applied joint hypocenter determination (JHD) to improve absolute locations, and then applied the double-difference relative location algorithm to the JHD output. These steps resolved th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Many events with a useable signal-to-noise ratio up to 50 kHz were recorded and AEs with magnitudes as small as MW-5.3 were detected. A catalogue of ~1.02 million seismic events collected from 10 July 2011 to 25 March 2012 was used to study the frequency-magnitude distribution of acoustic emissions, , the formation of damage structures ahead of the mining front, Moriya et al (2015), the unexpectedly frequent occurrence of very small repeating earthquakes, Naoi et al (2016), quasi-static growth of a slip-patch on a pre-existing fault and the properties of the rupture zone revealed by repeating events, Yamaguchi et al (2018). found that a Gutenberg-Richter law with b  1.2 was valid between MW -3.7 and 0 for acoustic emissions around the mining front, where MW is the moment magnitude.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Many events with a useable signal-to-noise ratio up to 50 kHz were recorded and AEs with magnitudes as small as MW-5.3 were detected. A catalogue of ~1.02 million seismic events collected from 10 July 2011 to 25 March 2012 was used to study the frequency-magnitude distribution of acoustic emissions, , the formation of damage structures ahead of the mining front, Moriya et al (2015), the unexpectedly frequent occurrence of very small repeating earthquakes, Naoi et al (2016), quasi-static growth of a slip-patch on a pre-existing fault and the properties of the rupture zone revealed by repeating events, Yamaguchi et al (2018). found that a Gutenberg-Richter law with b  1.2 was valid between MW -3.7 and 0 for acoustic emissions around the mining front, where MW is the moment magnitude.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Acoustic emission (AE)/seismicity is important for evaluating the stability of geological structures; for instance, the delineation of fracture systems from AE activity in geothermal reservoirs is indispensable for thermal energy extraction [1]. The stability evaluation of fractures during hydraulic stimulation in geothermal reservoirs is necessary to avoid inducing large AE events, where the relationship between large AE events and the pore-pressure distribution in reservoirs is studied [2]. The stability of geological structures is also important from the viewpoint of disaster prevention.…”
Section: Introductionmentioning
confidence: 99%
“…The studies assess (Korobiichuk, 2013;Korobiichuk & Iskov, 2013;Pershin & Ulyakov, 2015;Moriya et al, 2015;Bakka & Ilchenko, 1992;Karasev & Bakka, 1997;Korobiichuk et al, 2016a, b;Sobolevskyi et al, 2016;Kosolapov, 1990) that drilling takes 50-80% of the total time of block stone mining. Thus, the increase of the time spent on drilling can considerably reduce the mining works efficiency and, as a result, it can reduce the overall profitability.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the increase of the time spent on drilling can considerably reduce the mining works efficiency and, as a result, it can reduce the overall profitability. The main criteria to evaluate the efficiency of mining are the cracks of a massif (Moriya et al, 2015;Bakka & Ilchenko, 1992;Karasev & Bakka, 1997;Korobiichuk et al, 2016a, b;Sobolevskyi et al, 2016;Kosolapov, 1990;Mosch et al, 2011;Caranassios et al, 2000;Rahimi & Nygaard, 2015;Luodes & Sutinen, 2011) which are estimated by means of different factors. Specific fracturing is one of the main factors which, along with a blocks output, is used to evaluate the deposit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation